A cemented carbide material for water jet nozzle and preparation method thereof

By regulating the amount of HfC added and combining with the SPS system, a cemented carbide material with WC+HfC powder was prepared, which solved the problem of insufficient hardness and wear resistance in the application of high-pressure water drill nozzles, and achieved a combination of high hardness, good processing performance and corrosion resistance.

CN116240438BActive Publication Date: 2025-03-14HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211681281.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-03-14
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

Existing cemented carbide materials are difficult to meet the hardness and wear resistance requirements in high-pressure water drill nozzle applications, and at the same time they are prone to corrosion and oxidation in harsh environments, resulting in reduced wear resistance and corrosion resistance.

Method used

By regulating the amount of HfC added and combining with the SPS system, a cemented carbide material of WC+HfC powder was prepared, and sintered using SPS technology to achieve a combination of density and high hardness.

Benefits of technology

The prepared cemented carbide material has high relative density, ultra-high hardness, high strength and good processing performance, meets the use requirements of water drill nozzles, and improves wear resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004019495850000051
    Figure BDA0004019495850000051
  • Figure BDA0004019495850000052
    Figure BDA0004019495850000052
  • Figure BDA0004019495850000061
    Figure BDA0004019495850000061
Patent Text Reader

Abstract

The present invention provides a cemented carbide material for a water jet nozzle and a preparation method thereof. The cemented carbide material is prepared from a WC+HfC powder mixture by SPS, and based on 100wt.% of the total weight of the powder mixture, the powder mixture contains: 97.0wt.% to 99.75wt.% of WC powder and 0.25wt.% to 3.0wt.% of HfC powder. The cemented carbide material has high relative density, ultra-high hardness, high strength and good processing performance, and can meet the use requirements of a water jet nozzle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of powder metallurgy, and relates to a superhard cemented carbide material and a preparation method thereof, and more specifically, to a cemented carbide material for a water jet nozzle and a preparation method thereof. Background Art

[0002] In 1968, Dr. Norman Franz, a professor at the University of Michigan, invented high-pressure water jet cutting technology, also known as water jet cutting. In 1974, Flow Corporation of the United States successfully applied pure water jet cutting systems to industrial production. In the 1980s, the United States took the lead in advancing water abrasive jet cutting technology to the practical stage, making the cutting objects more extensive. Among the many cutting methods, only high-pressure water jet cutting belongs to cold cutting, which has many advantages: it can perform one-time cutting processing of materials in any curve, and the products after cutting do not need or are easy to be processed again, which is convenient, flexible and widely used; it does not use toxic or harmful gases or liquids, and does not produce toxic substances or steam; the cutting seam does not produce heat-affected zones or mechanical deformation; it can process materials that cannot be processed or are difficult to process by other processing methods, such as ceramics, composite materials, chemical fibers, heat-sensitive materials, etc.; it is safe, environmentally friendly, fast and efficient. Taking laser cutting as an example, although laser is better than water jet cutting in terms of cutting speed in thin plate cutting, the cost of laser cutting is high in metal cutting above 16mm, and heat affected zone is still generated around the cutting seam of laser cutting. Water jet cutting of metal materials can generally reach a thickness of 30 to 100mm or more, and has no effect on the material.

[0003] The working principle of high-pressure water jet is to use ultra-high pressure booster to gradually pressurize the liquid to 200-400MPa, and then form a jet with a speed of up to 1000m / s and great kinetic energy through a nozzle with a diameter less than 0.2mm, forming a high-energy water jet, which is sprayed onto the surface of the workpiece and destroys it. Water jet cutting with abrasives such as quartz sand, aluminum oxide, and corundum makes the water jet have the characteristics of a saw blade, and the cutting force is greatly improved, which can cut almost any hard material.

[0004] Due to the harsh working requirements of high-pressure water jets, the performance requirements for water jet nozzle materials are extremely high. The hardness of commonly used high-pressure water jet nozzle materials is required to be greater than 2700HV. At the same time, the material is required to have a very high relative density, no defects such as holes and cracks, and good processing performance and impact resistance.

[0005] Traditional cemented carbide will reduce the hardness and mechanical properties of cemented carbide due to the addition of a binder phase. And in harsh environments, these binders are more easily corroded and oxidized than the hard phase, which also reduces its wear resistance and corrosion resistance. Binder-free WC (tungsten carbide) based cemented carbide refers to a WC cemented carbide material that does not contain or contains less than 0.5wt% Co. Compared with traditional cemented carbide, binder-free WC based cemented carbide has better wear resistance, corrosion resistance, excellent polishing and other superior mechanical properties. However, tungsten carbide is a high melting point carbide (2870℃). In the absence of a binder phase, it is very difficult to obtain a dense binder-free cemented carbide using traditional sintering methods.

[0006] Studies have shown that reducing the grain size of WC sintering powder can reduce its sintering temperature, while achieving grain refinement, increasing hardness, and improving mechanical properties; however, finer WC powder is more prone to grain growth during sintering and densification, and adding HfC (hafnium carbide) as an inhibitor can effectively inhibit its grain growth; Spark Plasma Sintering (SPS) has the advantages of rapid temperature rise and fall and lower sintering temperature, avoiding grain growth and coarsening from the sintering process. Summary of the invention

[0007] The purpose of the present invention is to make up for the shortcomings of existing research, adjust the amount of HfC added and combine with the SPS system to provide a cemented carbide material for water jet nozzles and a preparation method thereof, and produce a cemented carbide for water jet nozzles with excellent performance. The cemented carbide material has high relative density, ultra-high hardness, high strength and good processing performance, and can meet the use requirements of water jet nozzles.

[0008] According to a first aspect of the present invention, there is provided a cemented carbide material for a water jet nozzle, wherein the cemented carbide material is prepared from a WC+HfC powder mixture by SPS, and based on 100wt.% of the total weight of the powder mixture, the powder mixture comprises: 97.0wt.% to 99.75wt.%, preferably 98.0wt.% to 99.5wt.% of WC powder, 0.25wt.% to 3.0wt.%, preferably 0.5wt.% to 2.0wt.% of HfC powder.

[0009] Preferably, the relative density of the cemented carbide material is not less than 99.9%.

[0010] Preferably, the cemented carbide material contains no other impurity phases except the main phase.

[0011] Preferably, the hardness of the cemented carbide material is 2750HV to 2850HV.

[0012] Preferably, the fracture toughness of the cemented carbide material is 5.0 MPa·m 1 / 2 ~8.2MPa·m 1 / 2 , more preferably 7.0 MPa·m 1 / 2 ~8.0MPa·m 1 / 2 .

[0013] According to a second aspect of the present invention, there is provided a method for preparing a cemented carbide material for a water jet nozzle according to the present invention, which comprises the following steps:

[0014] 1) Powder mixing: WC powder and HfC powder are put into a planetary ball mill for mixing, and the obtained mixed powder is vacuum dried. Based on 100wt.% of the mixed powder, the powder mixture contains: 97.0wt.% to 99.75wt.% of WC powder and 0.25wt.% to 3.0wt.% of HfC powder;

[0015] 2) Mold filling: The alloy powder obtained in step 1) is placed in a graphite female mold and pre-pressed using a hydraulic press with a pre-pressing pressure of 5 to 20 MPa;

[0016] 3) Sintering: Place the assembled graphite mold in the SPS system, set the axial pressure to 10MPa-50MPa, evacuate to below 10Pa, and sinter with electricity; set the heating rate to 30℃-100℃ / min, and the sintering temperature to 1600℃-1900℃, preferably 1700℃-1850℃; end the sintering after keeping warm for 0-5min, and cool with the furnace;

[0017] 4) Sampling: The samples are taken out by a hydraulic press, and the graphite on the surface of the samples is removed by sand blasting to obtain cemented carbide materials.

[0018] Preferably, the WC powder is a commercial pure phase powder with a purity of not less than 99.9% and a powder particle size of 0.1 to 1.0 μm.

[0019] Preferably, the HfC powder is a commercial pure phase powder with a purity of not less than 99.9% and a powder particle size of 0.1 to 1.0 μm.

[0020] Preferably, the addition ratio of HfC is 0.5 wt.% to 2.0 wt.%.

[0021] Preferably, the vacuum drying temperature ranges from 60 to 90° C., and the drying time ranges from 20 to 48 hours.

[0022] Preferably, the mixed powder is placed at the center of the graphite mold.

[0023] Preferably, the graphite female mold is separated from the powder by a graphite bushing, and the graphite pressing head is separated from the powder by a graphite sheet; and a layer of graphite felt for heat preservation is wrapped around the assembled graphite mold.

[0024] Further preferably, when the sintering temperature is ≤1400°C, the axial pressure is 10-20MPa; when the sintering temperature is greater than 1400°C and less than or equal to 1500°C, the pressure is increased to 20-50MPa, preferably 30-50MPa; constant pressure sintering is performed at the target pressure until sintering is completed.

[0025] Preferably, in step 3), the heating rate is set to 30-100° C. / min.

[0026] Preferably, the relative density of the cemented carbide block material obtained according to the method of the present invention is not less than 99.9%, and the phase contains no other impurity phase except the main phase.

[0027] Preferably, the hardness of the cemented carbide material obtained according to the method of the present invention is 2750HV to 2850HV.

[0028] Preferably, the fracture toughness of the cemented carbide material obtained by the method of the present invention is 7.0 MPa·m 1 / 2 ~8.0MPa·m 1 / 2 .

[0029] The present invention has the following beneficial effects:

[0030] The present invention provides a method for preparing a cemented carbide block material for a water jet nozzle. The mixed powder is prepared using commercial WC powder and HfC powder as raw materials, and then the mixed powder is prepared using SPS technology. The method has a simple process, a short production process, and is environmentally friendly. The prepared cemented carbide material has high relative density, ultra-high hardness, high strength and good processing performance, and can meet the use requirements of water jet nozzles. DETAILED DESCRIPTION

[0031] The present invention is further described below by way of examples, but the embodiments of the present invention are not limited thereto.

[0032] In the following examples, the graphite bushing is first matched with the graphite female mold, and then the lower pressure head is placed in the graphite female mold, and a piece of graphite sheet is placed to fit the pressure head; then the mixed powder according to the proportion is loaded into the graphite female mold; finally, the graphite sheet and the upper pressure head are placed in sequence, and the hydraulic press is used to apply pre-pressure and maintain pressure; after the above work is completed, the mold is wrapped with high-temperature graphite felt. The size of the graphite mold and the pressure head is determined by the size of the sample to be prepared.

[0033] The spark plasma sintering system used in the following embodiments is from SINTER LAND Co., Ltd. of Japan, and the models are LABOX-350 and LABOX-6020. Spark plasma sintering (SPS) includes pulsed power-on pressure sintering, electric field assisted sintering, pulsed current rapid sintering, etc. It should be noted that the sintering of cemented carbide materials for water jet nozzles using the method of the present invention and equipment of other manufacturers and models is also within the scope of the present invention.

[0034] The density results in the following examples were measured using the Archimedes displacement method;

[0035] The hardness test was obtained using a Vickers hardness tester, and the average value of 5 to 10 tests was taken as the final result; the fracture toughness test followed the international standard ISO 28079-2009 "Hardmetals-Palmqvist toughness test", measuring and calculating the total length of the four cracks at the indentation tip, and calculating the fracture toughness K based on the Vickers hardness value of the sample under the indentation. IC .

[0036] Example 1

[0037] The hard alloy block material for the water jet nozzle of φ20 mm×20 mm was prepared according to the following steps, wherein WC∶HfC=99.0∶1.0:

[0038] 1) Powder mixing: 100 g of the powder weighed in the above weight ratio is placed in a planetary ball mill for ball milling. The abrasive is a carbide ball, the ball-to-material ratio is 5:1, the ball milling speed is 300 r / min, and the ball milling time is 24 h. The powder after ball milling is subjected to high-temperature vacuum drying at a drying temperature of 80°C for 24 h.

[0039] 2) Mold filling: The alloy powder obtained after drying in step 1) is placed in a graphite female mold and pre-pressed using a manual hydraulic press.

[0040] 3) Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 20MPa, evacuate to below 10Pa, and start sintering with power on; set the heating rate to 70℃ / min, and the sintering temperature to 1850℃; end the sintering after 2 minutes of heat preservation, and cool with the furnace. When the temperature reaches 1400℃, increase the pressure to 50MPa.

[0041] 4) Sampling: The sample is taken out by a hydraulic press, and the graphite on the surface of the sample is removed by sandblasting to obtain a cemented carbide block material for a water jet nozzle. The specific performance parameters are shown in Table 1.

[0042] Table 1: Performance test results of cemented carbide materials prepared in Example 1

[0043]

[0044] Example 2

[0045] The hard alloy block material for the water jet nozzle of φ50m×30mm was prepared according to the following steps, wherein WC∶HfC=98.5∶1.5:

[0046] 1) Powder mixing: 1000 g of the composite powder weighed in proportion is placed in a planetary ball mill for ball milling. The abrasive is a carbide ball, the ball-to-material ratio is 5:1, the ball milling speed is 300 r / min, and the ball milling time is 24 h. The powder after ball milling is dried at high temperature in a vacuum at a drying temperature of 80°C for 36 h.

[0047] 2) Mold filling: The alloy powder obtained after drying in step 1) is placed in a graphite female mold and pre-pressed using a hydraulic press.

[0048] 3) Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 10MPa, evacuate to below 10Pa, and start sintering with power on; set the heating rate to 50℃ / min, and the sintering temperature to 1800℃; end the sintering after 3 minutes of heat preservation, and cool with the furnace. When the temperature reaches 1400℃, increase the pressure to 40MPa.

[0049] 4) Sampling: The sample is taken out by a hydraulic press, and the graphite on the surface of the sample is removed by sandblasting to obtain a cemented carbide block material for a water jet nozzle. The specific performance parameters are shown in Table 2.

[0050] Table 2: Performance test results of cemented carbide materials prepared in Example 2

[0051]

[0052] Example 3

[0053] The cemented carbide block material for a water jet nozzle of φ100m×20mm was prepared according to the following steps, wherein WC∶HfC=99.5∶0.5:

[0054] 1) Powder mixing: 2500g of the composite powder weighed in proportion is placed in a planetary ball mill for ball milling. The abrasive is a carbide ball, the ball-to-material ratio is 4:1, the ball milling speed is 200r / min, and the ball milling time is 48h. The powder after ball milling is dried at high temperature in a vacuum at a drying temperature of 80°C for 36h.

[0055] 2) Mold filling: The alloy powder obtained after drying in step 1) is placed in a graphite female mold and pre-pressed using a hydraulic press.

[0056] 3) Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 20MPa, evacuate to below 10Pa, and start sintering with power on; set the heating rate to 60℃ / min, and the sintering temperature to 1850℃; end the sintering after 5 minutes of heat preservation, and cool with the furnace. When the temperature reaches 1400℃, increase the pressure to 50MPa.

[0057] 4) Sampling: Take out the sample using a hydraulic press, and remove the graphite on the surface of the sample by sandblasting to obtain a cemented carbide block material that meets the requirements for a water jet nozzle. The specific performance parameters are shown in Table 3.

[0058] Table 3: Performance test results of cemented carbide materials prepared in Example 3

[0059]

[0060] Comparative Example 1

[0061] The cemented carbide block material for a water jet nozzle of φ80 mm×10 mm was prepared according to the following steps, wherein WC∶HfC=95.0∶5.0:

[0062] 1) Powder mixing: 1000 g of the composite powder weighed in proportion is placed in a planetary ball mill for ball milling. The abrasive is a carbide ball, the ball-to-material ratio is 4:1, the ball milling speed is 200 r / min, and the ball milling time is 48 h. The powder after ball milling is dried at high temperature in a vacuum at a drying temperature of 80°C for 36 h.

[0063] 2) Mold filling: The alloy powder obtained after drying in step 1) is placed in a graphite female mold and pre-pressed using a manual hydraulic press.

[0064] 3) Sintering: Place the assembled graphite mold in the SPS sintering system, set the initial axial pressure to 20MPa, evacuate to below 10Pa, and start sintering with power on; set the heating rate to 50℃ / min, and the sintering temperature to 1800℃; end the sintering after 3 minutes of heat preservation, and cool with the furnace. When the temperature reaches 1400℃, increase the pressure to 50MPa.

[0065] 4) Sampling: Take out the sample using a hydraulic press, and remove the graphite on the surface of the sample by sandblasting to obtain a cemented carbide block material for a water jet nozzle. The specific performance parameters are shown in Table 4.

[0066] Table 4: Performance test results of cemented carbide materials prepared in Comparative Example 1

[0067]

Claims

1. A cemented carbide material for a water jet nozzle, wherein: The cemented carbide material is prepared by SPS sintering a WC+HfC powder mixture, based on 100wt.% of the total weight of the powder mixture, the powder mixture comprises: 97.0wt.%~99.75wt.%WC powder, 0.25 wt. % to 3.0 wt. % HfC powder.

2. The cemented carbide material for water jet nozzle according to claim 1, wherein: The content of the WC powder is 98.0wt.% to 99.5wt.%.

3. The cemented carbide material for water jet nozzle according to claim 1, wherein: The content of the HfC powder is 0.5 wt.% to 2.0 wt.%.

4. The cemented carbide material for a water jet nozzle according to claim 1, wherein: The relative density of the cemented carbide material is not less than 99.9%.

5. The cemented carbide material for a water jet nozzle according to any one of claims 1 to 4, wherein: The hardness of the cemented carbide material is 2750HV to 2850HV.

6. The cemented carbide material for a water jet nozzle according to claim 5, wherein: The fracture toughness of the cemented carbide material is 5.0 MPa·m 1 / 2 ~8.2MPa·m 1 / 2 .

7. The cemented carbide material for a water jet nozzle according to claim 5, wherein: The fracture toughness of the cemented carbide material is 7.0 MPa·m 1 / 2 ~8.0MPa·m 1 / 2 .

8. The method for preparing a cemented carbide material for a water jet nozzle according to any one of claims 1 to 7, comprising the following steps: 1) Powder mixing: WC powder and HfC powder are put into a planetary ball mill for mixing, and the obtained mixed powder is vacuum dried. Based on 100wt.% of the mixed powder, the powder mixture contains: 97.0wt.% to 99.75wt.% of WC powder and 0.25wt.% to 3.0wt.% of HfC powder; 2) Mold filling: The alloy powder obtained in step 1) is placed in a graphite female mold and pre-pressed using a hydraulic press with a pre-pressing pressure of 5 to 20 MPa; 3) Sintering: Place the assembled graphite mold in the SPS system, set the axial pressure to 10MPa-50MPa, evacuate to below 10Pa, and sinter with electricity; set the heating rate to 30℃-100℃ / min, and the sintering temperature to 1600℃-1900℃; end the sintering after keeping warm for 0-5min, and cool with the furnace; 4) Sampling: The samples are taken out by a hydraulic press, and the graphite on the surface of the samples is removed by sandblasting to obtain cemented carbide materials.

9. The method according to claim 8, wherein: The sintering temperature in step 3) is 1700°C to 1850°C.

10. The method according to claim 8, wherein: The purity of the WC powder is not less than 99.9%, and the powder particle size is 0.1-1.0 μm; The purity of the HfC powder is not less than 99.9%, and the powder particle size is 0.1-1.0 μm.

11. The method according to claim 8, wherein: The vacuum drying temperature ranges from 60 to 90° C., and the drying time ranges from 20 to 36 hours.

12. The method according to claim 8, wherein: The mixed powder is placed at the center of the graphite mold.

13. The method according to claim 8, wherein: The graphite female mold and the powder are separated by a graphite bushing, and the graphite pressure head and the powder are separated by a graphite sheet; the outer periphery of the assembled graphite mold is wrapped with a layer of graphite felt for heat preservation.

14. The method according to claim 8, wherein: When the sintering temperature is ≤1400°C, the axial pressure is 10-20MPa; when the sintering temperature is greater than 1400°C and less than or equal to 1500°C, the pressure is increased to 20-50MPa; constant pressure sintering is performed at the target pressure until sintering is completed.

15. The method according to claim 14, wherein: When the sintering temperature is greater than 1400° C. and less than or equal to 1500° C., the pressure is applied to 30 to 50 MPa.

16. The method according to claim 8, wherein: In step 3), the heating rate is set to 30-100° C. / min.